THE EFFECT OF ZOZIBINI TUNZI'S SELF-IMAGE ON INSTAGRAM ACCOUNTS ON YOU C 1000 PRODUCT BRAND IMAGE FOR EAST KALIMANTAN TOURIST AMBASSADOR ASSOCIATION - Indira Apriliza; Hairunnisa Hairunnisa; Kezia Arum Sary (SEAN Institute, 2023)
The purpose of this study was to find out how significant and influential Zozibini Tunzi's self-image on her Instagram account is on the YOU C 1000 product brand image. is quantitative, and the type of research used in the form of a survey in collecting data takes samples from the population, namely users of Instagram accounts who follow accounts of daughters and East Kalimantan tourism ambassadors. The sampling technique uses a purposive sample and uses the Slovin formula, which produces 70 people as respondents. The data analysis technique used is descriptive, classical assumption test, simple linear regression analysis, coefficient of determination, and hypothesis testing. Based on the results of the answers from the respondents on the entire self-image variable Zozibni Tunzi (X) a percentage was obtained with a result of 4.32% which can be said to be included in the very good category. And in the results of the overall answer to the brand image variable, getting a percentage with result of 4.33% can be said to be very good. Based on the results of the t-test, the results of Zozibini TUnzi's self-image influence the brand image. This is evident from the results of the t-count test, namely tcount > ttable (5.365) > 1.996. Based on the coefficient of self-image determination, it influences brand image by 50.2%.